Suppression of molten salt corrosion by plasma sprayed Ni3Al coatings - Yasir, Sarah; Endrino, José L.; Guillén, Elena; Aria, Adrianus Indrat (Springer, 2021)
Corrosion behaviour of stainless steel 347 was investigated in a molten nitrate salt (60 wt% NaNO3 + 40 wt% KNO3) immersion at 565 °C for up to 3000 h. A growth of stratified oxide layers consisting of NaFeO2, Fe2O3 and Fe3O4 was observed on the stainless steel surface with a constant gravimetric corrosion rate of ~ 0.4 µm/year. The feasibility of using Ni3Al coatings deposited by means of air plasma spray for suppression of corrosion was investigated. Ni3Al coatings were observed to undergo a fast oxidation with a corrosion rate of ~ 2.7 µm/year in the first 500 h, and subsequently stabilise between 500 and 3000 h with no observable changes in microstructure, composition and weight at a corrosion rate of ~ 0.02 µm/year. The results presented in this study strongly suggest that Ni3Al coating suppresses the formation of oxide layers on the surface of stainless steel substrates and can be used as protection against corrosion in the presence of molten nitrate salts, which is of relevance to thermal energy storage applications.
Keywords: Molten nitrate salts; Stainless steel corrosion; Ni3Al coatings; Air plasma spray; Corrosion resistant coatings